Light transit systems proceedings of the symposium on the potential of light transit systems in British cities organized by the Institution of Civil Engineers and held in Nottingham on 14-15 March 1990 - North, B. H. (Thomas Telford, 1990)
Light transit systems are becoming popular and likely to be a major factor in reducing traffic congestion and pollution in cities. This title provides commentary on funding, engineering feasibility, public consultation, environmental impact, safety legal aspects and operation, drawing on experience in Europe Tyne and Wear, and London's Docklands.
Keywords: Street-railroads -- Great Britain -- Congresses.; elektronické knihy; electronic books